Citizen Science, Education, and Learning: Challenges and Opportunities - Roche, Joseph; Bell, Laura; Galvão, Cecília; Golumbic, Yaela N.; Kloetzer, Laure; Knoben, Nieke; Laakso, Mari; Lorke, Julia; Mannion, Greg; Massetti, Luciano; Mauchline, Alice; Pata, Kai; et al. (Frontiers in Sociology, 2020)
Citizen science is a growing field of research and practice, generating new knowledge and understanding through the collaboration of citizens in scientific research. As the field expands, it is becoming increasingly important to consider its potential to foster education and learning opportunities. Although progress has been made to support learning in citizen science projects, as well as to facilitate citizen science in formal and informal learning environments, challenges still arise. This paper identifies a number of dilemmas facing the field — from competing scientific goals and learning outcomes, differing underlying ontologies and epistemologies, diverging communication strategies, to clashing values around advocacy and activism. Although such challenges can become barriers to the successful integration of citizen science into mainstream education systems, they also serve as signposts for possible synergies and opportunities. One of the key emerging recommendations is to align educational learning outcomes with citizen science project goals at the planning stage of the project using co-creation approaches to ensure issues of accessibility and inclusivity are paramount throughout the design and implementation of every project. Only then can citizen science realise its true potential to empower citizens to take ownership of their own science education and learning.